3 ( 3 1 + tan 1 ∘ ) ( 3 1 + tan 2 ∘ ) ⋯ ( 3 1 + tan 5 8 ∘ ) ( 3 1 + tan 5 9 ∘ )
The above product can be written as c d a b , where a , c are prime numbers. Then find a + b + c + d upto 2 decimal places.
Bonus :
Try to generalize (I think you'll get what I'm saying once you solve the problem).
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can show that ( tan 3 0 ∘ + tan α ) ( tan 3 0 ∘ + tan ( 6 0 ∘ − α ) ) = 3 4 , using the ideas that you've presented.
Very nice proof. Just one thing. I think the denominator of the 6th line is a bit wrong. If its not could you explain that part.
Log in to reply
Yes sorry, it was a lot wrong. I've fixed it now thank you.
P = 2 r = 1 ∏ 2 9 T ( 3 1 + tan r ° ) ( 3 1 + tan ( 6 0 − r ) ° )
T = 1 / 3 + 3 1 A ( tan r ° + tan ( 6 0 − r ) ° ) + ( tan r ° ) ( tan ( 6 0 − r ° ) )
A = tan r ° + tan ( 6 0 − r ) ° = ( 1 − ( tan r ° ) ( tan ( 6 0 − r ° ) tan r ° + tan ( 6 0 − r ° ) ) ( 1 − ( tan r ° ) ( tan ( 6 0 − r ° ) ) = 3 ( 1 − ( tan r ° ) ( tan ( 6 0 − r ° ) )
∴ T = 4 / 3
P = 2 r = 1 ∏ 2 9 ( 3 4 )
= 2 ( 3 4 ) 2 9 = 3 2 9 2 5 9
Therefore 2 + 5 9 + 3 + 2 9 = 9 3 .
I don't know why, but we both have alike solutions many times
Log in to reply
Ya... I have this similarity with many of the guys here on brilliant and it's kinda' cool... :-)
Rishabh cool... I just love ur solutions. It motivates me to improve myself..ty
Combine the terms from the beginning and the end. The general term can be written as ( 3 1 + tan ( A ) ) ( 3 1 + tan ( 6 0 ° − A ) ) = 3 1 + 3 1 ( tan ( A ) + tan ( 6 0 ° − A ) + tan ( A ) tan ( 6 0 ° − A ) ) = 3 1 + 3 1 ( tan ( A + 6 0 ° − A ) ) ( 1 − tan ( A ) tan ( 6 0 ° − A ) ) + tan ( A ) tan ( 6 0 ° − A ) = 3 1 + 1 = 3 4 But the product term for A = 3 0 ° is 3 2 . We see that for all A = 3 0 ° the product on multiplication becomes 3 2 9 4 2 9 finally multipying by 3 2 and 3 also we get it as 3 2 9 2 5 9 hence the answer is 2 + 3 + 5 9 + 2 9 = 9 3
By. g e n e r a l i s e I mean instead of 6 0 ° take it as some B and add tan ( B ) 1 to make the product term as A = 1 ° ∏ B − 1 ° ⎝ ⎛ tan ( B ) 1 + tan ( B − A ) ⎠ ⎞ and check the middle term once. Try for B = 3 0 ° the middle term is amazing
Problem Loading...
Note Loading...
Set Loading...
Use the identity:
tan A + tan B = cos A sin A + cos B sin B = cos A cos B sin A cos B + sin B cos A = cos A cos B sin ( A + B )
3 ( 3 1 + tan 1 ° ) ( 3 1 + tan 2 ° ) . . . . . . ( 3 1 + tan 5 8 ° ) ( 3 1 + tan 5 9 ° )
= 3 ( tan 3 0 ° + tan 1 ° ) ( tan 3 0 ° + tan 2 ° ) . . . . . . ( tan 3 0 ° + tan 5 8 ° ) ( tan 3 0 ° + tan 5 9 ° )
= 3 ( cos 3 0 ° cos 1 ° sin ( 3 0 ° + 1 ° ) ) ( cos 3 0 ° cos 2 ° sin ( 3 0 ° + 2 ° ) ) . . . . . ( cos 3 0 ° cos 5 8 ° sin ( 3 0 ° + 5 8 ° ) ) ( cos 3 0 ° cos 5 9 ° sin ( 3 0 ° + 5 9 ° ) )
= 3 ( cos 3 0 ° 1 ) 5 9 ( cos 1 ° sin 3 1 ° ) ( cos 2 ° sin 3 2 ° ) . . . . ( cos 5 8 ° sin 8 8 ° ) ( cos 5 9 ° sin 8 9 ° )
We also have: sin 9 0 ° − x ° = cos x ° :
. . . = 3 ( 3 2 ) 5 9 sin 8 9 ° sin 8 8 ° . . . sin 3 2 ° sin 3 1 ° sin 3 1 ° sin 3 2 ° . . . sin 8 8 ° sin 8 9 °
= 3 ( ( 3 ) 5 9 2 5 9 ) = ( 3 ) 5 8 2 5 9 = 3 2 9 2 5 9
a = 2 , b = 5 9 , c = 3 , d = 2 9 ⇒ a + b + c + d = 2 + 5 9 + 3 + 2 9 = 9 3